2014
DOI: 10.3892/ol.2014.2013
|View full text |Cite
|
Sign up to set email alerts
|

Isocitrate dehydrogenase mutation is associated with tumor location and magnetic resonance imaging characteristics in astrocytic neoplasms

Abstract: The molecular subsets of glioma behave in biologically distinct ways. The present study detected isocitrate dehydrogenase (IDH) 1 and IDH2 mutations in glioma to analyze whether IDH-mutated gliomas are situated in certain preferential areas and to investigate their correlation with magnetic resonance imaging (MRI) characteristics. A series of 193 patients with astrocytic neoplasms (111 diffuse and 82 anaplastic astrocytomas), grouped according to prelabeled anatomical structures and the risk of surgery, were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

20
100
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(125 citation statements)
references
References 38 publications
20
100
2
3
Order By: Relevance
“…Another study demonstrated that IDH1-mutated gliomas were predominantly located in a single lobe and were more likely to have a unilateral growth pattern, sharp tumor margin, homogeneous signal intensity, and less contrast enhancement on MR imaging. 27 In the present study, we also found that tumor contrast enhancement was associated with IDH1 status. Tumors accompanied by mutant IDH1 were less likely to show contrast enhancement on MR images compared with tumors without IDH1 mutation.…”
Section: Discussionsupporting
confidence: 76%
“…Another study demonstrated that IDH1-mutated gliomas were predominantly located in a single lobe and were more likely to have a unilateral growth pattern, sharp tumor margin, homogeneous signal intensity, and less contrast enhancement on MR imaging. 27 In the present study, we also found that tumor contrast enhancement was associated with IDH1 status. Tumors accompanied by mutant IDH1 were less likely to show contrast enhancement on MR images compared with tumors without IDH1 mutation.…”
Section: Discussionsupporting
confidence: 76%
“…22 Alternatively, methods such as MR perfusion and diffusion tensor imaging have been shown to correlate with IDH-mutation status. [23][24][25] Provided that these techniques, particularly spectroscopy, continue to advance at their present rate, radiographic identification of 1p/19q status could be all that is necessary to categorize WHO grade II and III infiltrating gliomas by imaging. 18,[26][27][28][29] Our finding of an association between lower ADC values with 1p/19q codeletion has previously been described in small studies.…”
Section: Discussionmentioning
confidence: 99%
“…29,37,38 Sharper margins and less contrast enhancement by MR imaging have been associated with features of ALTϩ tumors, including mutant IDH1, mutant tumor protein p53 (TP53), or proneural tumors. 13,16,18,20,39,40 Considering that most ALTϩtumors in this study had mutant IDH1 or IDH2, MR imaging features of ALT may be due to mutant IDH. The expansive T1/FLAIR VASARI feature had greater significance when tumors were compared based on IDH mutant status rather than telomere maintenance subtype.…”
Section: Discussionmentioning
confidence: 99%
“…Isocitrate dehydrogenase 1 (IDH1) mutations, O6-methylguanine methyltransferase (MGMT) promoter methylation, and epidermal growth factor receptor overexpressing tumors have been correlated with MR imaging features. 13,[15][16][17][18][19] That tumor biology influences imaging features is further evident in studies that investigate subgroups of glioblastomas based on multiple gene expression differences. 20 This study aimed to determine whether MR imaging features were associated with the telomere maintenance mechanism and tumor-associated macrophage content-based subtypes.…”
mentioning
confidence: 99%